2020
DOI: 10.1021/acs.chemmater.0c03788
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Synthesis of Cu–M–S (M = V, Cr, Mn) Nanocrystals by Tuning the Copper Precursor Reactivity

Abstract: New ternary and higher order inorganic materials are needed for a large variety of applications, yet their synthesis still represents a chemistry challenge. Herein, we focus on the synthesis of Cu−M−S nanocrystals (where M = V, Cr, Mn) via a wetchemistry route and investigate their formation mechanisms. We reveal that the interplay between the copper precursor and the thiophilicity of the transition metal M is the key for the synthesis of pure phase Cu−M−S nanocrystals under the same reaction conditions. In pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…More recently, we extended this approach to CuCrS 2 and Cu 2 MnS 2 . Taking CuCrS 2 as an example, Cu x S ( x = 1, 2) and Cr y S z ( y = 2, 3 and z = 3, 4) were isolated as the reaction intermediates when CuI and chromium acetylacetonate (Cr­(acac) 3 ) were used as the Cu and Cr precursors, respectively (Figure ).…”
Section: In-situ Forming Nanocrystals As Reaction Intermediates In Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, we extended this approach to CuCrS 2 and Cu 2 MnS 2 . Taking CuCrS 2 as an example, Cu x S ( x = 1, 2) and Cr y S z ( y = 2, 3 and z = 3, 4) were isolated as the reaction intermediates when CuI and chromium acetylacetonate (Cr­(acac) 3 ) were used as the Cu and Cr precursors, respectively (Figure ).…”
Section: In-situ Forming Nanocrystals As Reaction Intermediates In Co...mentioning
confidence: 99%
“…(B) HAADF-STEM image elemental mapping performed on the aliquot extracted after 3 min of reaction between CuI and Cr­(acac) 3 . Additional details on the mechanistic studies are reported in ref . The scale bars are 20 nm.…”
Section: In-situ Forming Nanocrystals As Reaction Intermediates In Co...mentioning
confidence: 99%
“…[6,9,[22][23][24][25] Commonly, the micro and nanostructured Cu-based materials with controlled particle size, chemical composition, and surface morphology are synthesized by solid-state or solution-based techniques. [26][27][28] Most of these methods involve organic surfactants as structure-directing agents which can modify, even mask, the surface chemistry of the micro and nanostructures. Moreover, electrodes of these materials can be fabricated by deposition onto suitable support in the presence of polymeric binders (e.g., Nafion or polytetrafluoroethylene).…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, micro and nanostructured Cu catalysts are of special consideration owing to their superior selectivity and performance for several electrocatalytic reactions [6,9,[22][23][24] . Commonly, the micro and nanostructured Cu-based materials with controlled particle size, chemical composition, and surface morphology are synthesized by solid-state or solution-based techniques [25][26][27] . Most of these methods involve organic surfactants as structure-directing agents which can modify, even mask, the surface chemistry of the micro and nanostructures.…”
Section: Introductionmentioning
confidence: 99%